A comparison of breast and lung doses from chest CT scans using organ‐based tube current modulation (OBTCM) vs. Automatic tube current modulation (ATCM). Issue 5 (3rd May 2021) - Layman, Rick R.; Hardy, Anthony J.; Kim, Hyun J.; Chou, Ei Ne; Bostani, Maryam; Cagnon, Chris; Cody, Dianna; McNitt‐Gray, Michael
Abstract: Purpose: The purpose of this work was to estimate and compare breast and lung doses of chest CT scans using organ‐based tube current modulation (OBTCM) to those from conventional, attenuation‐based automatic tube current modulation (ATCM) across a range of patient sizes. Methods: Thirty‐four patients (17 females, 17 males) who underwent clinically indicated CT chest/abdomen/pelvis (CAP) examinations employing OBTCM were collected from two multi‐detector row CT scanners. Patient size metric was assessed as water equivalent diameter ( Dw ) taken at the center of the scan volume. Breast and lung tissues were segmented from patient image data to create voxelized models for use in a Monte Carlo transport code. The OBTCM schemes for the chest portion were extracted from the raw projection data. ATCM schemes were estimated using a recently developed method. Breast and lung doses for each TCM scenario were estimated for each patient model. CTDIvol ‐normalized breast ( nDbreast ) and lung ( nDlung ) doses were subsequently calculated. The differences between OBTCM and ATCM normalized organ dose estimates were tested using linear regression models that included CT scanner and Dw as covariates. Results: Mean dose reduction from OBTCM in nDbreast was significant after adjusting for the scanner models and patient size ( P = 0.047). When pooled with females and male patient, mean dose reduction from OBTCM in nDlung was observed to be trending after adjusting for the scanner model and patient size ( P = 0.085). Conclusions: One specific manufacturer's OBTCM was analyzed. OBTCM was observed to significantly decrease normalized breast relative to a modeled version of that same manufacturer's ATCM scheme. However, significant dose savings were not observed in lung dose over all. Results from this study support the use of OBTCM chest protocols for females only.